NILAI DAKWAH DALAM BUDAYA SAIYYANG PATTUQDUQ BAGI MASYARAKAT KABUPATEN MAJENE - Nurhanuddin (Istiqra: jurnal hasil penelitian, 2025)
This study aims to examine the forms of practice of the Saiyyang Pattuqduq cultural tradition and to identify the da‘wah values embedded within it among the people of Majene Regency. It’s a cultural heritage of the Mandar community that has been preserved across generations and remains closely connected to Islamic teachings and local religious expressions. This research adopts a qualitative approach with a phenomenological design to explore how the community understands and experiences the religious meanings of this tradition in their social life. Data were collected through direct observation, in-depth interviews with key informants, and documentation as supporting evidence. The data were analyzed using four phenomenological stages: horizontalization to identify significant statements related to participants’ experiences, textual description to present detailed accounts of these experiences, structural description to examine the contextual conditions in which they occur, and the synthesis of meanings to capture the essence of the phenomenon. The findings reveal that Saiyyang Pattuqduq is practiced in various religious and social events, including messawe totammaq (Qur’an completion ceremonies), weddings, guest welcoming ceremonies, and cultural festivals. The tradition embodies key dawah values moral values are reflected in honesty and cooperation within the community. Sharia values are manifested through adherence to Islamic dress codes. This study highlights the importance of preserving Saiyyang Pattuqduq as a form of cultural da‘wah that strengthens religious awareness, social cohesion, and the cultural identity of the Majene community.